Uji Coba Perangkap Telur Pembunuhan Diri - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK A modified autocidal ovitrap was developed as an alternative method for vector control of Dengue Hemorrhagic Fever. It was one to the fact that development of vaccine and specific treatment of the virus are not available at recent time. This type of vector control has some advantages compared to the currently use in the program such as malathione fogging and elimination of Aedes aegypti breeding places. Two stages testing have been carried out to measure efficacywhich are laboratory and field testing . laboratory testing has been replicated three times and it was found to be statistically significant efficacious. Result of the field trial which was done for the duration of nine weeks revealed that this method could decrease Breteau Index up to 7.5 percent during the trials attracted. Increased of autocidal ovitrap - index proved that musqoitoes attracted to lay its eggs to the device.